Destino do corpo morto: cremação em São Paulo, século XX - Cardoso, Fabiana Franco (2013)
In August 1974, there was the inauguration of the Crematorium Jayme Augusto Lopes, popularly known as Crematorium Alpine Village. Thus, the city of São Paulo began offering two destinations for the dead body: burial and cremation. To track the origin of cremation in our city was required in addition to consulting the press, read the Minutes of the City Council, bills and a text of the Public Civil Action on missing politicians found in the ditch in Cemetery Perus. This study focused on the period between the years 1967 and 1974, revealed the position of Brazilian ecclesiastical and political authorities on the practice crematory, measures the contribution of the military to the installation of the first crematorium in the capital, the role of the press in disclosure of government plans, negotiations between the Church, doctors and politicians to define adequate conditions for the population of the city, and promote reflection on the constant transformation of the city of São Paulo in search of modernity